FXRS: Fast X-Ray Spectrum-Simulator Theory and Software Implementation (Communications in Computational Physics, 2018)
We propose a simple, computationally efficient scheme for an X-ray spectrumsimulator. The theoretical models describing the physical processes involved areemployed in our Monte Carlo software in a coherent way, paving the way for straightforwardfuture improvements. Our results compare satisfactorily to experimental resultsfrom literature and to results from dedicated simulation software. The simplicity,excellent statistical errors, and short execution time of our code recommend it for intensiveuse in X-ray generation simulations.